151k views
0 votes
The functions f and g are defined as follows.

f(x) = -2x+2
g(x) = 2x² – 3x
Find f (6) and g(-4).
W
Simplify your answers as much as possible.

f(6) =?
g(-4) =?

User Mbpaulus
by
5.5k points

1 Answer

3 votes
f(6)= -10 because -2(6) is -12. -12+2 = -10
g(4)= 44 because pemdas mean we do exponents first so -4(-4)= 16. 16x2= 32. -4(-3)=12. 32+12=44
User Mervyn Lee
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.